The role of metabolic enzymes in the development of resistance in cocoa mirid, Helopeltis Theivora Waterhouse. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2005)
Topical bioassays were conducted to evaluate the toxicity of deltamethrin, cypermethrin, y-HCH and chlopyrifos against 3 populations of H. theivora namely the cocoa populations (Serdang. Selangor) and Sungai Tekam, Pahang) and tea population (Banting. Selangor). The synergistic effects of piperonyl butoxide (PBO), maleic acid diethyl ether (MADE) and s.s.s-tributyl phosphorotrittlioate (DEF) were also tested using similar technique. Based on the LDso values, the toxicity ofthe insecticide tested for the Serdang and Sungai Tekam populations were chlopyrifos > y-HCH > cypermethrin > delWnethrin; forthe Banting population was y-HCH > cypermethrin > chlorpyrifos > deltamethrin. The most toxic insecticide was chlopyrifos with LD50 value of 3.028 x 10-2mg/l for the Sungai Tekam population. The synergism of PBO on cypermethrin was higher compared to other insecticides tested.